2015
DOI: 10.1007/s10571-015-0276-5
|View full text |Cite
|
Sign up to set email alerts
|

Huperzine A Alleviates Oxidative Glutamate Toxicity in Hippocampal HT22 Cells via Activating BDNF/TrkB-Dependent PI3K/Akt/mTOR Signaling Pathway

Abstract: Oxidative glutamate toxicity is involved in diverse neurological disorders including epilepsy and ischemic stroke. Our present work aimed to assess protective effects of huperzine A (HupA) against oxidative glutamate toxicity in a mouse-derived hippocampal HT22 cells and explore its potential mechanisms. Cell survival and cell injury were analyzed by MTT method and LDH release assay, respectively. The production of ROS was measured by detection kits. Protein expressions of BDNF, phosphor-TrkB (p-TrkB), TrkB, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…miR-382, microRNA-382; miR-NC, miRNA mimic negative control; RT-qPCR, reverse transcription quantitative polymerase chain reaction; CCK-8, Cell Counting Kit-8.tumour-suppressing roles in RB, at least in part by regulating BDNF.miR-382 inhibits PI3K/AKT signalling in RB. BDNF is involved in PI3K/AKT signalling pathway regulation(35,36).…”
mentioning
confidence: 99%
“…miR-382, microRNA-382; miR-NC, miRNA mimic negative control; RT-qPCR, reverse transcription quantitative polymerase chain reaction; CCK-8, Cell Counting Kit-8.tumour-suppressing roles in RB, at least in part by regulating BDNF.miR-382 inhibits PI3K/AKT signalling in RB. BDNF is involved in PI3K/AKT signalling pathway regulation(35,36).…”
mentioning
confidence: 99%
“…Our data showed that SD (12 hr) and SCF could upregulate TrkB/CREB/ERK signaling, which suggest that the increased BDNF mitigates depressive symptoms mainly by binding to TrkB, leading to autophosphorylation of TrkB tyrosine residues and activation of downstream signaling molecules, including the ERK known to phosphorylate CREB. In addition, BDNF/TrkB downstream signaling includes activation of Ras/ERK and PI3K/AKT pathways (Luo et al, ; Mao, Zhou, Li, & Liu, . Basic and clinical studies demonstrated that BDNF related PI3K/AKT signaling pathway was involved in the stress‐induced depression and antidepressant‐induced improvement (Wang et al, ; Zeng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the protective effects of HupA, a highly selective and potent AChE inhibitor, against neuronal damage have been well proven in multiple in vitro neuronal models [26,30,38,39] , whether and how this active natural product can directly ameliorate iron overload-induced neuronal damage has not yet been clarified. The most notable aspects of the present study include: 1) the significant effect of HupA on alleviating multifaceted iron overload-induced malignant changes in primary cortical neurons, and 2) the finding that the classical AChEinhibiting effect of HupA may not contribute to its protection against iron-overload-induced neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increasing numbers of studies have demonstrated that HupA can ameliorate oxidative stress and mitochondrial dysfunction [20][21][22] . First, HupA significantly suppresses ROS overproduction and lipid peroxidation in Aβ- [23,24] , H 2 O 2 - [25] and glutamate [26] -stimulated cellular models. Second, HupA also markedly ameliorates oxidative stress in chronic cerebrally hypoperfused and aged rats [27,28] and attenuates mitochondrial dysfunction in APP/PS1 transgenic mice [29] and rats after intracerebral hemorrhage (ICH) [30] .…”
Section: Acta Pharmacologica Sinicamentioning
confidence: 96%